Transplante de tecido ovariano criopreservado e restauração do metabolismo ósseo em ratas castradas - Silva, Lígia Helena Ferreira Melo (2017)
Despite the use of cryopreservation of ovarian tissue to restore fertility, there are no published studies addressing the effects of this technique on bone metabolism. This study aims to evaluate the ovarian results of the ovarian tissue graft heel after vitrification and reimplanted in the omentum of rats, to compare estradiol levels in these rats at different stages according to the presence or absence of this tissue and to evaluate the effects on the bone metabolism of such reimplantation the present study was performed in 27 rats aged 11 to 12 weeks and weighing 200-300g, a period in which there is establishment of hormonal maturity. All animals underwent bilateral oophorectomy to induce hypoestrogenism and the ovaries were vitrified. Autotransplantation occurred in two different periods according to each group: after 1 week (group A, n = 8) or after 1 month (group B, n = 19) counted from the first intervention (before oophorectomy). Serum estradiol assays and histological analysis of ovarian tissue and tibia were performed: before oophorectomy (basal), at the end of the surgical castration period (after oophorectomy) and one month after transplantation (replantation). In groups A and B, the mean cortical thickness of the tibia was 0.463 ± 0.14 mm (mean ± SD) at the baseline, 0.360 ± 0.14 mm after oophorectomy and 0.445 ± 0.17 mm at 1 month post reimplantation (p < 0.005). In addition, mean trabecular thickness was 0.050 ± 0.08 mm (mean ± SD) at baseline, 0.022 ± 0.08 mm after oophorectomy and 0.049 ± 0.032 mm at 1 month after replantation (p <0.005). Regarding estradiol levels, it was observed that estradiol levels were significantly lower after castration (group A: 8.10 ± 0.4 ng / dL, group B: 11.80 ± 1.2 ng / dL). baseline (group A: 23.43 ± 2.44 ng / dL, group B: 25.90 ± 8.10 ng / dL), and returned to normal levels after replantation in both groups (between 20 and (Group A: 20.47 ± 1.45 ng / dL, group B: 20.97 ± 1.41 ng / dL, p = 0.013). There was a difference between estradiol between groups A and B, this recovery being greater in group A (not statistically significant). The presence of atretic follicles, primordial follicles and corpus luteum follicles was observed in approximately 81.5% of the animals (group a: n = 7/8, 87%, group b: n = 15/19, 78.9%, p = 0.080) showing that the reimplantation site is valid. According to these results, cryopreserved ovarian tissue transplantation not only restored ovarian hormonal function, but reestablished the initial bone parameters. These results may suggest that ovarian reimplantation in women has beneficial effects on bone metabolism. Key words: Ovarian tissue. Autotransplant. Menopause. Bone metabolism.